2017
DOI: 10.5897/ajar2016.11824
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post-harvest losses of Warqe food products along the supply chain in Central Ethiopia

Abstract: Post-harvest food loss is a global problem but it is more critical in the food-insecure countries. Food waste occurs at different levels in the food supply chain from production through post-harvest handling to consumption. The presented paper aims at an assessment of post-harvest food loss of warqe foods along the supply chain and identified hot spots of the losses in the chain. Warqe (Ensete ventricosum (Welw) Cheesman) is banana like plant and it used as a food and non-food applications. Kocho and bulla are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…Moreover, the products they sell are usually in dried forms therefore cases of spoilages encountered by other marketers are not severe. The study agrees with that of Ashenafi et al (2017) in their study on assessment of post-harvest loss of food product along the supply chain in Central Ethiopia who reported that poor quality products for processing and physical loss during cleaning, washing and drying activities were the main reasons for losses at processing operation. The incidences of mould and deterioration in quality due to exposure to air were another cause of loss at the processor level.…”
Section: Distance Taken From Farm/purchase Point To Point Of Sale Of ...supporting
confidence: 91%
“…Moreover, the products they sell are usually in dried forms therefore cases of spoilages encountered by other marketers are not severe. The study agrees with that of Ashenafi et al (2017) in their study on assessment of post-harvest loss of food product along the supply chain in Central Ethiopia who reported that poor quality products for processing and physical loss during cleaning, washing and drying activities were the main reasons for losses at processing operation. The incidences of mould and deterioration in quality due to exposure to air were another cause of loss at the processor level.…”
Section: Distance Taken From Farm/purchase Point To Point Of Sale Of ...supporting
confidence: 91%